Ambivalence resolution in meaning reconstruction grief therapy: an exploratory study - Braga, Cátia Sofia Macedo (2021)
In psychotherapy, ambivalence may be conceptualized as a conflict between two distinct motivations: one that is favorable to change (pro-change) and another that favors the maintenance of a problematic pattern (pro status quo). Previous studies identified two processes by which clients resolve this conflict: imposing the innovative part and silencing the problematic one (dominance), and establishing negotiations between the innovative and the pro status quo parts (negotiation). The present exploratory study examined ambivalence resolution in a sample of clients diagnosed with complicated grief. Results revealed that, in recovered cases, negotiation increases and dominance decreases from the beginning until the middle sessions of therapy and the opposite tendency is observed from the middle to the final sessions. Unchanged cases reveal an overall high proportion of dominance and an overall low proportion of negotiation. These results are partially divergent from those reported in previous studies with samples of clients diagnosed with major depression.